1994
DOI: 10.2166/wst.1994.0298
|View full text |Cite
|
Sign up to set email alerts
|

Continuous high-rate removal of chromate in a fluidised bed without sludge generation

Abstract: The objective of the work presented here was to investigate the catalysing effect of iron oxyhydroxide on the redox reaction between ferrous iron and chromate. This was done in a bench-scale upflow reactor containing an expanded sand medium (fluid-bed reactor), where continous chemical addition, reaction and solid-liquid separation take place. Removal efficiencies of chromate in excess of 99% were attainable on spiked tapwater corresponding to an outlet concentration of 0.01 mg/l. Chromate polluted groundwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The flow velocity has been found to be less than 3 m/h in a fixed-bed [15,16], which is low. Using an FBR has been studied to adsorb heavy metals from wastewater [14,17,18] and found that the velocity was 6-30 m/h. The flow rate in an FBR is higher than that in a fixed bed, and the adsorption time is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The flow velocity has been found to be less than 3 m/h in a fixed-bed [15,16], which is low. Using an FBR has been studied to adsorb heavy metals from wastewater [14,17,18] and found that the velocity was 6-30 m/h. The flow rate in an FBR is higher than that in a fixed bed, and the adsorption time is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Lopez et al (11) examined the efficiency of alginate beads containing Mycrocystis species for uranium and copper adsorption in a fluidized loop reactor and approximately 30−65% adsorption has been reported. Aktor (12) and Nielson et al (13) have highlighted the effective removal of metal ions in fluidized bed without sludge generation. Stirred tank reactors for successful removal of Fe, 3+ Pb, 2+ Cd 2+ and Cu 2+ had been investigated by Sag and Kutsal (14) and Ozer et al (15).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the fluidized-bed reactor (FBR) technique process has been used as an alternative treatment method for heavy metal removal [10][11][12][13][14][15]. The process of crystallizing CaCO 3 in an FBR was applied in the softening of drinking water [10].…”
Section: Introductionmentioning
confidence: 99%